Insidious postoperative Aspergillus niger graft aortitis. (2020) - Marro, M.; Atzeni, F.; La Torre, M.W.; Attisani, M.; Belloro, S.; De Rosa, F.G.; Rinaldi, M.
Highlights: Fungal endocarditis/aortitis. The first case of polyethylene-terephthalate (PETE) graft aortitis caused by A. niger. Transoesophageal echocardiography (TEE). Abstract: Fungal endocarditis/aortitis is an uncommon yet emerging entity accounting for 2% to 4% of all cases of infective endocarditis and continues to be associated with a poor prognosis. We present the first case of polyethylene-terephthalate (PETE) graft aortitis caused by A. niger, a rare fungal agent. Early diagnosis with frequent transoesophageal echocardiography (TEE) and a prompt surgical intervention coupled with optimal antifungal therapy are still the only option to reduce the exceedingly high mortality and morbidity.